HOW TO TALK ABOUT LEGAL HISTORY WITHOUT BEING A HISTORIAN? HISTORIOGRAPHICAL CONSIDERATIONS ON PENALTY AND PUNISHMENT - Belúcio Nogueira, Raul Ferreira; Ganzert Weinhardt, Otávio Augusto (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2024)
It is not rare at all to find criminal law handbooks, courses, and even academic texts discrediting criminal legal history achievements on shared issues. This article is an effort to facilitate this dialogue by offering some criminal legal history references to Brazilian criminalists willing to address the several pasts criminal law has for itself. Based solely on literature and consolidated historiography, the results differ drastically from the “historical introductions” manuals and other similar literature have presented in the past century. What we offer is an invitation to legal history to the detriment of legal modern mythologies.